Аудит производственных запасов на базе ПКРП «Белая Русь» - Земляная, Н.Н. (Культура народов Причерноморья, 2013)
В статье отражена роль аудита производственных запасов в процессе формирования
себестоимости продукции, финансовых результатов, налогооблагаемой прибыли. С целью оценки уровня
риска аудитору необходимо оценить систему внутреннего контроля за организацией учета по данному
разделу на предприятии. Автором изучен перечень основных процедур на каждом этапе аудита
производственных запасов. Информация о состоянии учета производственных запасов важна для
обеспечения контроля за их сохранностью, снижения налоговых рисков, а также для принятия
оптимальных управленческих решений.
Ключевые слова: аудит, производственные запасы, система внутреннего контроля, методика аудит У статті відображена роль аудиту виробничих запасів у процесі формування собівартості
продукції, фінансових результатів, оподатковуваного прибутку. З метою оцінки рівня ризику аудитору
необхідно оцінити систему внутрішнього контролю за організацією обліку з даного розділу на
підприємстві. Автором вивчений перелік основних процедур на кожному етапі аудиту виробничих
запасів. Інформація про стан обліку виробничих запасів важлива для забезпечення контролю за їх
збереженням, зниження податкових ризиків, а також для прийняття оптимальних управлінських
рішень.
Ключові слова: аудит, виробничі запаси, система внутрішнього контролю, методика аудиту This article reflects the role of the audit of inventory in the process of production costs, financial
results, taxable income. Business transactions on the accounting of inventory related to transactions with a high
level of risk. In order to assess the level of risk the auditor needs to evaluate the system of internal control over
the organization of accounting under this section for the enterprise. The whole extent of audit procedures for
verification, in fact, can be divided into several groups: Audit of availability and security of inventory, audit
movement of inventory, checking the correctness of tax inventories. The author studied a list of key audit
procedures in each group. During the analysis of the state of internal controls and accounting systems of
inventory on PKRP "Belaya Rus" was compiled by the author profile tests to assess the organization of
accounting for PKRP "White Russia" were tested. As a result of the procedures developed by the example of a
going concern are not found evidence of non-compliance of accounting applicable law. Information about the
status of records of inventory is important to maintain control over their safety, reduce tax risks, as well as to
make better management decisions.
Keywords: auditing, inventory, internal control, audit methodology